Surface Modification with Silane Coupling Agent on Tensile Properties of Natural Fiber Composite - Willy Artha Wirawan; Sofyan Arief Setyabudi; Teguh Dwi Widodo; Moch. Agus Choiron (University of Muhammadiyah Malang, 2017)
Biocomposite is an innovation of renewable material in engineering made from the bark fiber of waru (Hibiscus tiliaceus, the bark is environmentally friendly and has the potential to be developed. The purpose of this study is to modify biocomposite by adding methacryloxypropyltrimethoxysilane-coupling agent on waru bark fiber (Hibiscus tiliaceus) as an effort to improve tensile properties. Waru bast fibers, as reinforcement, were prepared by alkali procces using 6% NaOH solution for 120 minutes and then added 0.75% coupling agent and ordered using continous fibers with 0°/0°, 0°/90° and 45°/45° orientation. After that, the Biocomposites were formed with a polyester matrix using Vacuum Pressure Resin Infusion (VAPRI) method. The results of SEM tested showed the quality improvement of the bonds bringing significant impact on the tensile properties of the waru bark biocomposite. On the continous fiber 0°/90° orientated showed that the highest strength was 401.368 MPa, while biocomposites with 45°/45° orientation has lowest tensile strength of 65.243 MPa